Assessment and Mitigation of Risk of Agricultural Sector Unsustainability in East Java Province: Based on Vulnerability Aspects of Internal Characteristics of Workers - Fuad Ramdhan Dewantoro (East Java Economic Journal, 2025)
The problem of the declining trend in the percentage of labor and the contribution of the agricultural sector to ADHB GRDP in the last decade indicates the risk of future unsustainability that has a negative impact on the economy of East Java. This study aims to assess the risk of unsustainability of the agricultural sector in East Java based on the vulnerability of internal characteristics of workers. The research method combines cluster analysis and logistic regression on 8 internal characteristics of agricultural workers to calculate the probability of vulnerability. Impact was assessed from historical data on the decline in the number of workers and the contribution of the agricultural sector to GRDP. The risk level was obtained by multiplying the values of opportunity and impact. The results show that East Java Province as a whole has a high level of risk of agricultural sector unsustainability, with details of 3 districts/cities having a very low level of risk, 6 low, 21 high, and 8 very high. Further analysis revealed that areas with higher risk levels generally have agricultural workers with characteristics of older age, low education level, minimal use of technology, low income, short working hours, long working period, low financial bookkeeping, and high informal status. The research conclusions emphasize the importance of prioritizing risk management in areas with high/very high risk levels while still paying attention to areas with very low/low risk levels. Risk management suggestions include: Preventive is carried out in areas with high opportunities and impacts, focusing on improving workers' skills and knowledge and encouraging the adoption of technology. Directive is carried out for areas with small opportunities but large impacts, conducting.